Diagnosis of Diamond-Blackfan anemia in adulthood: case series and review of the literature - Francesco Versino; Paola Bianchi; Elisa Fermo; Wilma Barcellini; Bruno Fattizzo (Orphanet Journal of Rare Diseases)
Abstract Diamond–Blackfan anemia (DBA) is a rare constitutional inherited bone marrow failure syndrome (iBMF) characterized by progressive severe non-regenerative anemia and congenital abnormalities. Diagnosis is made by identification of a DBA-causing variant, typically in a ribosomal protein gene. More than 99% of patients are diagnosed in the pediatric age, but clinical manifestation may be mild and severe anemia can occur later in the patient’s life. Moreover, the expanding availability of molecular testing is increasing the ability to identify DBA variants also in adults with a non-canonical DBA phenotype. Therefore, adult hematologists must maintain a high clinical suspicion and awareness towards possible DBA diagnosis in adulthood. In this context, the most common differential diagnoses are acquired BMFs such as pure red cell aplasia (PRCA) or hypoplastic myelodysplastic syndrome (MDS). Here, we present three adult patients diagnosed with DBA, where the identification of the causative mutation occurred several years from PRCA misdiagnosis or was made after screening for an affected relative. We also provide a review of 16 cases available in the literature and give hints on possible treatment strategies.